Liability of officials of business associations - PALCHUK Петро (Ius Modernum, 2023)
Introduction. The organizational and legal form of a limited liability company (LLC) makes it possible to form a flexible and effective system of corporate management, to ensure and control the receipt of income and the exercise of the will of the members of the LLC by officials. Problem. The determination of the legal status of the executive body members of the limited liability company (LLC) as well as their responsibility for their management of the company remains insufficiently researched from the point of view of the participation of companies in civil and other relations and requires the study of the sectoral affiliation of the responsibility of executive body members. The aim of the article is to determine, based on the analysis of Ukrainian legislation and the practice of its application, the legal nature of the executive body members’ liability in limited liability company (LLC); as well as the conditions under which they may be held liable for mismanagement. Methods. The philosophical (dialectical), general scientific (analysis and synthesis, systemic-structural, modeling, abstraction, formal-logical) methods as well as special methods of cognition used in jurisprudence (methods of interpretation of legal norms, legal-dogmatic, comparative-legal), etc. are applied. Results. It’s substantiated that the executive body members, when performing the duties assigned to them, should act in the interests of the limited liability company members, the company itself and its creditors. In case of provisions of the legislation and the statute violation as well as in case of improper performance of their official duties, the members of the executive body bear corporate responsibility, which has a civil law nature. Conclusions. If the actions of the executive body members contain a civil offense, they must bear civil liability. The culpability of the relevant official action (action or inaction) and other conditions of certain type legal responsibility must be proven, in particular, the cause-and-effect relationship between the illegal behavior of the responsible person and the existing losses of the company.